God bless - The Boyz; WARNER Music (Malaysia). (Kuala Lumpur : Warner Music, 1998)
Contains two pop tracks taken from the album Next Level.
CD 1 : God Bless (non rap version) / (3:15) -- God Bless (rap version) / (3:54).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English